Correlation between sex hormone levels and corneal hysteresis and resistance factor during menstrual cycle - Peyman, M.; Bakhtiari, A.; Voon, P.L.; Subrayan, V. (2014)
Purpose: To determine corneal biomechanical properties change during phases of the menstrual cycle and to correlate with sex hormone levels.